Kebutuhan Seksual Menjadi Penyebab Utama Tingginya Angka Perceraian (Doktrin: Jurnal Dunia Ilmu Hukum dan Politik, 2023)
In Islam, marriage is a sunnatullah that applies to every creature. Marriage cannot always achieve its essential goals, one of which can be seen in divorce. It can even be stated that the most sad event in marriage is divorce, so God really hates it. So the author raised the theme "Sexual Needs Are the Main Cause of High Divorce Rates". The type of research used in this paper is Library Research. Using primary data sources that use material from several books about sexual needs and books about divorce. Secondary material as support for this research uses books, articles, papers that discuss divorce caused by sexual needs. So, based on this research, it can be concluded that one of the factors that can influence a family to divorce, among others, is the dissatisfaction of one partner in sexual relations, resulting in the partner's inner income not being met. Biological factors that are not fulfilled by partners are the main factor in the high divorce rate, either because they do not get satisfaction from their partners or for various reasons.